Growth response of cabbage (Brassica oleracea) to TiO2 nanoparticles exposure in Inceptisol of north-western mid-hills of Himachal Pradesh - BRAR, PERMINDER SINGH; BHARDWAJ, GITIKA; KAUSHAL, RAJESH; BHARDWAJ, RAMESH KUMAR; SINGH, UPENDER; SHARMA, UDAY (The Indian Journal of Agricultural Sciences, 2025)
The experiment was conducted during 2020–21 and 2021–22 at Dr. Yashwant Singh Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh for assessing the effects of TiO2 (Titanium dioxide) nanoparticles on cabbage (Brassica oleracea L. var. capitata) growth, yield and economics under Agro-Climatic Zone- II of Himachal Pradesh. A field experiment was laid out in a randomized block dsesign (RBD) with three replications having 13 treatments , comprised of seed and foliar application of TiO2 nanoparticles (size <25 nm) combined with different nutrient sources. Results revealed that by the application of 100% RDN through integration of chemical fertilizers and vermicompost; the maximum plant height, spread and yield were recorded under seed treatment of TiO2 nanoparticles @1000 ppm. The findings have also demonstrated that the least number of days needed to attain 50% head maturity, total N content and N uptake was achieved with seed treatment of TiO2 nanoparticles @1000 ppm. Whereas, total P, K and Fe content; P and K uptake was recorded under foliar spray of TiO2 nanoparticles @1000 ppm. Among all the treatments, 1000 ppm concentration of TiO2 nanoparticles concluded with higher yield attributes and maximum benefit-cost ratio (3.76). When it comes to soil characteristics, the integration of chemical fertilizers and vermicompost resulted in improved physico-chemical and microbiological properties which, in general, may be profitable and sustainable for cabbage cultivation in Inceptisol of north-western mid-hills of Himachal Pradesh.